IDENTIFIKASI HAMA KELAPA SAWIT MENGGUNAKAN METODE CERTAINTY FACTOR - Widians, Joan Angelina; Rizkyani, Farahdina Nur (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2020)
The lack of knowledge of palm oil farmers and general public about pests in palm oil plants will result in a lack of crop yields on these plants. The resulted in the impact of many palm oil farmers who cut down trees as an effort to eradicate of pests. The limitations of an experts makes handling palm oil plan pests difficult so it is necessary to have an experts system that is able to identify pests of palm oil and how to control them based on knowledge given directly by human experts. The inference is Forward chaining by tracing the rules based on the answers of users. And then calculated by Certainty Factor method. The result of calculation is in the form of a percentage value of confidence and user can immediately find out the type of pests identified and how to control it. This research found 7 (seven) types of pests that attack palm oil are fire caterpillar Setothosea asigna, caterpillars Dasychira inclusa, bag caterpillar Metisa plana, horn beetle Oryctes rhinoceros, termite Coptotermes curvignathus, wild rat Rattus tiomanicus, dan wild pig Sus crofa. The biggest pest attact on palm oil is Termite Coptotermes Curvignathus is 88,8%